THE IMPACT OF INTEGRATED MICROLEARNING MEDIA IN STUDENT WORKSHEET IN PROBABILITY ON STUDENTS’ REASONING ABILITIES - Komariyatiningsih, Novi; Hartono, Yusuf; Ilma Indra Putri, Ratu; Hiltrimartin, Cecil (Prosiding Seminar Nasional Matematika dan Pendidikan Matematika, 2025)
This research aims to design a student worksheet based on microlearning media in probability for 10th-grade students. The worksheet was developed using microlearning-based Indonesia Realistic Mathematics Educaion approach using the culinary tourism context of Prabumulih City to help students learn the probability in 10th grade students and train their reasoning abilities. This research used the research and development method, which consists of two stages, namely, preliminary research and formative evaluation. The subjects of this research were 35 students of grade 10th SMAN 6 Prabumulih. Data were collected through observation, tests, and interviews. Data analysis shows that with the worksheet, students’ reasoning ability is sufficiently good. Therefore, it is included that students' worksheets in probability based on microlearning media support students' reasoning abilities.